The Shifting Paradigm of “Onlife Learning” in European Higher Education Institutes (HEIs): A Case of Working-Life Competence Development Best Practices - Rathod, Paresh; Kämppi, Pasi (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The digital transformations bring opportunities and challenges in modern societies, especially profound impact on the European higher education institutes (HEIs). Digital technologies and online learning are becoming increasingly common after the recent COVID-19 phenomenon. The continued digital technologies adoption in human lives has led to the emergence of a new approach to learning called “onlife learning.” “Onlife learning” emphasises the integration of formal and informal learning, using technology for lifelong learning, and the need for new skills and competencies. In HE, “onlife learning” is becoming more prevalent, however, there is no one-size-fits-all approach to training and skills development. The key competencies for “onlife learning” include digital literacy, critical thinking, and self-directed learning. These competencies can be developed through various approaches, including experiential learning, blended learning, problem solutions and online learning. The technologies play an important role in “onlife learning”. It is essential to support learners in developing their digital skills. This includes providing access and usage training to appropriate technologies, which is especially important to create opportunities for learners to practice their digital skills. The paper provides valuable insights into the best practices for training and skills development in “onlife learning” in European HEIs. The findings are the outcomes of the EU Innovation project ECOLHE. They can be used to inform the design of effective working-life training, skills and competencies development that support learners in developing the competencies they need to succeed in a rapidly changing digital world.